基于Alpha Shapes三维重建原理的机器人工作空间求解方法 - 范启忠; 陈是扦; 刁燕; 罗华; 王强 (Jixie chuandong)
The workspace is an important kinematics index of robot and workspace analysis of a surgical robot is a key link in structural optimization and surgery planning.First,the point cloud of workspace is generated by using the Monte Carlo method and the boundary extraction method of partitioning by angle is put forward to get the boundary points of the point cloud.On the basis of the boundary points,the Alpha Shapes algorithm is employed to reconstruct the workspace.Compared with conventional workspace surface solving method,this method has higher precision and better versatility,for it is convenient to adjust theαvalue according to different workspace types.Finally,the volume of the workspace is calculated with numerical integration method,a foundation for robot carrying out surgery is provided.